Influence of Attitudes and Cosmetic Advertisements on the Selection of Cosmetics Containing Harmful Ingredients by Adolescents in Medan City - Ratna Dianitami; R. Kintoko Rochadi; Nurmaini Nurmaini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cosmetics play a significant role in the daily routines, especially for teenagers in the city of Medan. However, concerns regarding the safety of cosmetics, particularly those containing harmful substances, are on the rise. This research aims to identify the attitudes and cosmetic advertisements influencing the selection of hazardous cosmetics by teenagers in Medan. Involving 385 respondents aged 17–22 in Medan, distributed across 18 districts, this study employs a cross-sectional approach and statistical analyses such as chi-square and multiple logistic regression to measure the impact of specific variables on the behavior of cosmetic selection among teenagers. The research findings indicate that attitudes and cosmetics advertisements play a crucial role in the decisions of cosmetic selection among teenagers. Therefore, actions to enhance positive attitudes, the availability of safe cosmetic products, and stricter regulation of cosmetic advertisements need to be considered. All of these measures are expected to assist teenagers in making wiser choices and supporting their health in selecting cosmetic products.